School of teaching Japanese, Korean, Mongolian and Indonesian languages - S. V. Chironov (Vestnik MGIMO-Universiteta)
School of teaching Japanese, Korean, Mongolian and Indonesian languages is a continuation of the synonymous department at Moscow state university. Teaching materials at the Department of Oriental languages are designed in such a way that make it possible to study not only these complex languages, but also the state and political system, history, culture and traditions of the countries the language. Articles of the department's members are published in various volumes of scientific papers both in Russia and abroad